(untitled) (Research, Society and Development, 2020)
Nurses increasingly assume leadership roles throughout the health care delivery chain and their responsibilities permeate the entire care process. The present study aims to know what the national and international literature has presented, in the period from 2015 to 2019, on the theme leadership in nursing in relation to palliative care. It is a reflective study. To support the reflection, a survey of the literature was carried out in the online databases Medical Literature Analysis and Retrieval System, Latin American and Caribbean Literature in Health Sciences and Scientific Electronic Library Online. The descriptors used were as follows: "Palliative care", "leadership" and "nursing". The search was carried out in February 2020, and four articles were selected that helped in the discussion. Leading nurses with knowledge in palliative care are essential for the success of care initiatives. Furthermore, it is necessary to establish links between the professional and the patient in order to guarantee qualified, comprehensive and continuous care, encompassing family / caregiver in a humanized, resolutive way, with quality and responsibility. The importance of leadership and the use of communication were identified as strategies that allow nurses to implement changes in order to provide quality palliative care. Nursing leadership in the face of palliative care arises naturally, since the nurse receives information from all members of the multidisciplinary team, being a link between all professionals, as well as between the family and the team.